Functional and Operator Variants of Jensen's, Chord's, and Mercer's Inequality - Pavia, Zlatko (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
The paper examines functional and operator variants of Jensen's, chord's, and Mercer's inequality with a convex function on the interval of real numbers. In this research we relied on general functional and operator forms of Jensen's inequality. Among others, corresponding means are also observed. The inequalities for operators are observed without operator convexity.